DETECTION OF POTATO VIRUS Y (PVY) BY REVERSE-TRANSCRIPTION LOOP-MEDIATED NUCLEIC ACID AMPLIFICATION (RT-LAMP) - Treder, Krzysztof; Chołuj, Joanna; Zacharzewska, Bogumiła; Mielczarek, Mateusz (Plant Breeding and Seed Science, 2017)
Potato virus Y (PVY), a type member of the genus Potyvirus (family Potyviridae), is currently the most important virus infecting the potato crop. PVY is also a dangerous pathogen of the tomato, pepper, and tobac-co. The reverse transcription loop-mediated amplification (RT-LAMP) is gaining recognition as a good alter-native to RT-PCR in diagnosing plant viruses. Here, we provide a detailed description of a simple protocol for fast and sensitive detection of PVY by the RT-LAMP assay, which can be easily adapted to detect other plant pathogens, harboring both RNA and DNA genomes.